1991
DOI: 10.1111/j.1349-7006.1991.tb01856.x
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Gelatin Particle Agglutination Test for Detection of Anti‐HTLV‐I Antibody

Abstract: Partial modifications of antigen components were made to improve the gelatin particle agglutination (PA) test for the detection of antibodies against human T cell leukemia virus type‐I. Envelope glycoproteins prepared by lentil lectin affinity chromatography were further added to the purified viral antigens to be coated on the gelatin particles. Comparative studies with a conventional PA test kit (Serodia ATLA) and indirect immunofluorescence assay showed that the specificity and sensitivity of the new PA test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

1991
1991
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(18 citation statements)
references
References 22 publications
1
16
0
1
Order By: Relevance
“…The controls included 1,458 patients aged ≥50 years, without any cancer or history of cancer, who were admitted to the Department of Medicine and Therapeutics, Ryukyu University Hospital, Okinawa, Japan, between 1991 and 2005. In all patients, serum anti-HTLV-1 antibody was measured by the gelatin particle agglutination method (Fujino et al 1991), infection of S. stercoralis was diagnosed using the agar plate culture method (Arakaki et al 1990), and liver flukes were diagnosed using the direct smear method. In 627 patients (115 patients with cancer and 512 patients without cancer), liver flukes were also diagnosed using the formalin-ether sedimentation method.…”
Section: Study Populationmentioning
confidence: 99%
“…The controls included 1,458 patients aged ≥50 years, without any cancer or history of cancer, who were admitted to the Department of Medicine and Therapeutics, Ryukyu University Hospital, Okinawa, Japan, between 1991 and 2005. In all patients, serum anti-HTLV-1 antibody was measured by the gelatin particle agglutination method (Fujino et al 1991), infection of S. stercoralis was diagnosed using the agar plate culture method (Arakaki et al 1990), and liver flukes were diagnosed using the direct smear method. In 627 patients (115 patients with cancer and 512 patients without cancer), liver flukes were also diagnosed using the formalin-ether sedimentation method.…”
Section: Study Populationmentioning
confidence: 99%
“…The particle agglutination test uses gelatin paricles sensitized with HTL V -1 antigens Fujino et al, 1991).…”
Section: Serological Detection Of Specifie Antibodiesmentioning
confidence: 99%
“…In this study we have demonstrated frequent positive reactions in the PA test for anti-HTLV-1 antibodies (Fujino et al, 1991) with sera derived from acute VZV infections. IgM antibodies are mostly responsible for this cross-reactivity.…”
mentioning
confidence: 94%